Quantitative risk allocation approach in public-private partnership projects - Valipour, Alireza (2015)
Risk allocation is an important factor in risk management to ensure successful achievement of the implementation of Public-Private Partnership projects (PPP). Several PPP projects have failed to meet budget, deadlines, and quality inspection. There are 327 unsuccessful PPP projects around the world and Malaysia is the second highest in East Asia with 22 failed projects. Inappropriate risk allocation has led to adversarial relationships between contracting participants and has consequently increased project cost, time and poor quality. Thus, it is very important for the public and private sector to choose a fair risk allocation in order to make strategic decisions. The aim of this study was to develop an optimal quantitative approach to enhance the equitable risk allocation in PPP projects. This study presents a Fuzzy Analytic Network Process model for equitable risk allocation which converts linguistic principles and solves the problem of independence and feedback between criteria and barriers using Analytic Network Process (ANP) method. Objective functions are then developed to minimize the total time, the cost of the project and maximize the quality while satisfying risk threshold constraints. The combinatorial nature of the risk allocation problem describes a multi-objective situation that can be simulated as a knapsack problem (KP). The formulation of the KP is described and solved by applying genetic algorithm. A total of 42 risks was identified and evaluated. The finding of this study shows "construction completion delay” was the most important risk with the highest rank. Finally, of 42 significant risks, 16 was allocated to the public sector, 11 were allocated to the private sector and 15 were shared between public and private sector as the best package of shared risks. The results of this investigation can be implemented by the government to enhance risk allocation process which may encourage the participation of the private sector through better risk allocation. As a conclusion, a new method has been developed regarding equitable quantitative risk allocation. It helps the project owners as well as contractors and subcontractors to better manage risk, cost and time savings and at the same time improve the overall quality of PPP projects